Fracture and mechanical properties of asphalt mixtures containing granular polyethylene terephthalate (PET). (30th October 2020) - Esfandabad, Amin Shams; Motevalizadeh, Seyed Mohsen; Sedghi, Reza; Ayar, Pooyan; Asgharzadeh, Seyed Mohammad
Highlights: Different granular contents of PET were incorporated into the conventional asphalt mixtures. Fracture, moisture, and rutting resistance of asphalt mixtures were assessed. Weibull probability distribution was fitted over the fracture data aimed at analyzing the probability of fracture. It was determined that the probability of fracture failure significantly increased due to the increase in PET contents. The inclusion of PET particles caused increasing the rutting and moisture resistance of the mixtures. Abstract: This study was conducted due to lack of comprehensive documentation on the fracture and mechanical properties of asphalt mixtures containing Polyethylene Terephthalate (PET) particles. To this end, PET granules were used to replace a specific portion of mineral aggregates (i.e., passing from sieve #4 and retained on sieve #8) with different contents including 0, 30, 50, 70 and 100%. In this regard, Indirect Tensile Strength (ITS), moisture sensitivity, Semi-Circular Bending (SCB), and wheel tracking tests have been carried out under different testing conditions. The Weibull model was also used to obtain a more detailed investigation of fracture data outcomes. The results showed that although the increased PET contents resulted in reduced ITS values, moisture resistance was enhanced. Improved resistance against rutting distress at 45 ℃ was also observed, indicating that using different PET contents could increase the stiffness of mixtures. Further, Weibull distribution indicated that the fracture failure at −20 ℃ was more probable than that of at 0 ℃. Additionally, fracture resistance was reduced when 30 and 50% PET included in the asphalt mixtures. However, increasing PET contents in the mixtures resulted in limited periods of tolerable fracture energy, and this, in turn, increased the probability of fracture failure.